On the use of the TMA Framework to promote self-adaptation capabilities in TalkConnect - Pereira, José D’Abruzzo; Ribeiro, João David; Pires, João; Moita, Pedro; Laranjeiro, Nuno; Vieira, Marco (Anais Estendidos do Latin-American Symposium on Dependable and Secure Computing (LADC), 2022)
Cloud applications are usually deployed in a third-party infrastructure, which follows a pay-per-use model. This is especially important to companies (such as Talkdesk) that have flexibility to adjust their infrastructure without needing to buy new hardware. However, the resources acquired should be adjusted to the demand at any given moment, on one hand to assure the right quality of service (i.e., resources should not be less than what is needed) and in the other hand to reduce costs (i.e., resources should not be more than what is required). TMA (Trustworthiness Monitoring & Assessment Framework) is a solution developed at the University of Coimbra that promotes self-adaptation capabilities to cloud applications. This paper presents a case on the use of TMA in TalkConnect, showcasing a collaboration between academia and industry. TalkConnect is a solution developed by Talkdesk to promote global interconnection to multiple telecommunication infrastructures.